“Vozes da comida”: práticas alimentares e escolas do campo - Segatto, Juliana de Abreu Otarão (2016)
This dissertation investigated via food two rural schools. These two rural schools belong to the countryside of a town in the state of Rio Grande do Sul. The aim of this study was to discuss the interfaces between subjective relationships (I-Alter-World), the food and health consumer practices in rural and school communities of a city in the countryside of Rio Grande do Sul. This was built from a descriptive qualitative design through participant observation with notes in a rural diary, semi-structured interviews and conversation circles allied to the drawing. Therefore, we prepared two articles. The first article takes as its starting point the eating habits of the food handlers of the surveyed rural schools, nominated in the environment of our research “lunch ladies", seeking to make connections between the legislation, specific public policies, theory and in locus and semi-structured observations. The purpose of this study was to reflect on public policies related to school foodways, from the “lunch ladies” discourse and feeding practices. The second article discusses the various knowledge about the food, from the 4th and 5th grades of Elementary School students' point of view, of two rural schools in the state of Rio Grande do Sul. We had interest in hearing what children residing in the countryside have to say about the food they consume. The aim of this study was to identify the feeding practices of children of the school community reflecting on the connections between desire, demand for food consumption and health. The analysis of both items were made from the Social Representation Theory (SRT) from the perspective of Critical Social Psychology (CSP). The analysis of all the material allowed us to see, in the first article, the invisibility and the lack of a specific place for the school lunch ladies. The second showed a mismatch in the speech of the children in relation to food. In the drawings it is evident the reified discourse and in the conversation circles what is the desire order. Students verbalize the (dis)taste of the school food, this not only by the typical local spice change, but the lack of salt that binds to affectivity. In addition, children bring about the relationship between food and health, an antinomic thought.